TINDAK TUTUR ILOKUSI DALAM â€œKUMPULAN CERITA RAKYAT MELAYU SAMBASâ€ OLEH CHAIRIL EFFENDY - Safitri, Eni; Syam, Christanto; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractSpeech is a process for someone to deliver message with specific intent and purpose to the interlocutor. Speech and its events are interrelated; both of events those exist in one process, known as the process of communication. Sambas Malay Folklore Collection was the data that provided in this study. Based on the data analysis, the results of this study as follows: (1) acting speech acts illocution as an assertive, directive, expressive, commissive, and declaration. (2) the meaning contained in every act of speech of illusion of assertive, directive, expressive, commissive, and declaration form and (3) lesson plan implementation. The result of analysis of Sambas Malay Folklore concluded, there were twenty-seven assertion of acute illusory acts, thirty data of the directive speech act, six data of not expressive, six data of the commissive speech acts, one data of the act of speech declaration and seventy acts of assertive illusion, directive, expressive, commissive, and declarative of meaning in every form of speech, and its lesson plan implementation of Sambas Malay Folklore as the learning material in the curriculum of 2013.Keywords: Discourse of Illocution, Meaning, Malay Sambas Folklore.